Green infrastructure strategies for sustainable coastal tourism: A SWOT–AHP analysis - I Wayan Thariqy Kawakibi Pristiwasa; I Nyoman Budiarta; Mohd Raziff Jamaluddin; Gina Alcoriza (Jurnal Fokus Manajemen Bisnis, 2026)
The Riau Archipelago in Indonesia possesses significant coastal and marine ecosystems that underpin tourism development. However, these assets are increasingly threatened by climate change, fragmented spatial planning, and unequal infrastructure provision. Grounded in sustainable tourism development theory, green infrastructure planning, and strategic management theory, this study aims to identify and prioritize green infrastructure-based strategies that enhance climate resilience and long-term tourism sustainability. Using a mixed-methods approach, primary data were collected through in-depth interviews, focus group discussions, and structured questionnaires involving 15 purposively selected stakeholders from government agencies, tourism operators, and environmental organizations. Secondary data were obtained from regional planning documents, tourism statistics, and environmental reports. SWOT analysis was applied to systematically identify internal strengths and weaknesses as well as external opportunities and threats related to green infrastructure integration. Subsequently, the analytical hierarchy process was employed to assign weights and rank 20 alternative strategies based on stakeholder judgments. The analysis produced an IFAS score of 2.71 and an EFAS score of 2.47, indicating a moderately favorable strategic position. The results highlight mangrove restoration and hybrid coastal protection as top priorities, while expanding the theoretical contribution by positioning green infrastructure as a crucial asset for destination competitiveness.